Cloaked Viruses and Viral Factors in Cutting Edge Exosome-Based Therapies - Dogrammatzis, Christos; Waisner, Hope; Kalamvoki, Maria (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles (EVs) constitute a heterogeneous group of vesicles released by all types of cells that play a major role in intercellular communication. The field of EVs started gaining attention since it was realized that these vesicles are not waste bags, but they carry specific cargo and they communicate specific messages to recipient cells. EVs can deliver different types of RNAs, proteins, and lipids from donor to recipient cells and they can influence recipient cell functions, despite their limited capacity for cargo. EVs have been compared to viruses because of their size, cell entry pathways, and biogenesis and to viral vectors because they can be loaded with desired cargo, modified, and re-targeted. These properties along with the fact that EVs are stable in body fluids, they can be produced and purified in large quantities, they can cross the blood–brain barrier, and autologous EVs do not appear to cause major adverse effects, have rendered them attractive for therapeutic use. Here, we discuss the potential for therapeutic use of EVs derived from virus infected cells or EVs carrying viral factors. We have focused on six major concepts: (i) the role of EVs in virus-based oncolytic therapy or virus-based gene delivery approaches; (ii) the potential use of EVs for developing viral vaccines or optimizing already existing vaccines; (iii) the role of EVs in delivering RNAs and proteins in the context of viral infections and modulating the microenvironment of infection; (iv) how to take advantage of viral features to design effective means of EV targeting, uptake, and cargo packaging; (v) the potential of EVs in antiviral drug delivery; and (vi) identification of novel antiviral targets based on EV biogenesis factors hijacked by viruses for assembly and egress. It has been less than a decade since more attention was given to EV research and some interesting concepts have already been developed. In the coming years, additional information on EV biogenesis, how they are hijacked and utilized by pathogens, and their impact on the microenvironment of infection is expected to indicate avenues to optimize existing therapeutic tools and develop novel approaches.